Effects of oral capsaicinoids and capsinoids supplementation on resistance and high intensity interval training - Jiménez-Martínez, P.; Ramirez-Campillo, R.; Flandez, J.; Alix-Fages, C.; Baz-Valle, E.; Colado, J. C. (Journal of Human Sport & Exercise, 2023)
Oral capsaicinoids and capsinoids supplementation has been studied recently for a plausible ergogenic impact on sports performance. However, non-aggregated literature has focused on the impact of this substances in healthy humans` performance. The aim of the present systematic review was to explore the effects of capsaicinoids and capsinoids on resistance training (RT) and HIIT exercise. Studies searches were performed in the PubMed/MEDLINE, Scopus and Web of Science electronic databases. Studies where healthy subjects consumed capsaicinoids or capsinoids acutely or chronically compared to placebo before a RT or HIIT intervention were included. The methodological quality of the included studies was assessed with PEDro checklist. A total of 7 excellent-good quality placebo-controlled trials (i.e., 5 RT and 2 HIIT experiments) were included. The most prevalent protocol used capsaicin (i.e., 6 capsacin and 1 capsiate studies) and acute (i.e., 5 of 7 interventions) supplementation designs. Positive effects were only noted for capsaicin in repetitions until failure (+14.4 to +21.7%), total weight lifted (+13.0 to +23.3%), perceived effort (-6.4%), fatigue index (+15.0%) and peak torque (+6.1%) compared to placebo. Neuromuscular HIIT variables (e.g., total and medium sprint time) were not highly affected by capsaicin except the time to reach 90% VO2 peak (+61.2%) and the number of efforts performed (+14.7%). Collectively, our findings suggest a positive effect of 12 mg of capsaicin on strength endurance, total weight lifted and perceived effort variables in healthy males after acute (i.e., 45 minutes pre-exercise) supplementation.